2017
DOI: 10.1038/s41598-017-04553-4
|View full text |Cite
|
Sign up to set email alerts
|

A High-Power Broadband Terahertz Source Enabled by Three-Dimensional Light Confinement in a Plasmonic Nanocavity

Abstract: The scope and potential uses of time-domain terahertz imaging and spectroscopy are mainly limited by the low optical-to-terahertz conversion efficiency of photoconductive terahertz sources. State-of-the-art photoconductive sources utilize short-carrier-lifetime semiconductors to recombine carriers that cannot contribute to efficient terahertz generation and cause additional thermal dissipation. Here, we present a novel photoconductive terahertz source that offers a significantly higher efficiency compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…[133][134][135][136] In this case, the THz generation occurs due to nonlinear optical processes 134 as well as the heat redistribution inside metal due to electron heating by an optical excitation. 137,138 However, the emitted THz power of the standalone metal metasurface is relatively low compared with the plasmonic PCA 69 and even to the surface photo-Dember THz emitter 136 and amounts, on average, to 0.15 mW, corresponding to an optical-to-THz conversion efficiency of up to 0.01% at 5.8 THz. 135 Furthermore, both metallic and dielectric metasurface configurations can be designed to effectively interact with THz radiation and thus can be used in ultrasensitive THz sensors, THz absorbers, highly selective THz detectors, tunable THz field modulators, [139][140][141][142] and THz mirrors, 143 as well as to control a wavefront at THz frequency, 144 etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[133][134][135][136] In this case, the THz generation occurs due to nonlinear optical processes 134 as well as the heat redistribution inside metal due to electron heating by an optical excitation. 137,138 However, the emitted THz power of the standalone metal metasurface is relatively low compared with the plasmonic PCA 69 and even to the surface photo-Dember THz emitter 136 and amounts, on average, to 0.15 mW, corresponding to an optical-to-THz conversion efficiency of up to 0.01% at 5.8 THz. 135 Furthermore, both metallic and dielectric metasurface configurations can be designed to effectively interact with THz radiation and thus can be used in ultrasensitive THz sensors, THz absorbers, highly selective THz detectors, tunable THz field modulators, [139][140][141][142] and THz mirrors, 143 as well as to control a wavefront at THz frequency, 144 etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the photocarriers are generated in very close proximity to the nanoantennas, and if a bias voltage is simultaneously applied, almost all of them can reach the nanoantennas and contribute to the THz emission. Yardimci et al 69 70 They demonstrated an SNR of 100 dB when operating with an optical pump power of 5 mW. However, as an optical power exceeds 5 mW, the sensitivity of the detector starts saturating, whereas the LT-GaAs-based PCA-detector exhibits higher responsivities working with the same optical pump.…”
Section: Metallic Metasurfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using distributed Bragg re°ector-based nanocavity, authors have achieved strong con¯nement of the optical beam and 4-mW terahertz power is reported in Ref. 68. In order to see the di®erences clearly, reported results of recent OPM studies are summarized in Table 5 and plotted in Fig.…”
Section: Photomixingmentioning
confidence: 98%
“…Terahertz time‐domain spectroscopy (THz‐TDS) employs short pulses of electromagnetic radiation, which have a broad terahertz frequency range (Skoog, Holler, & Crouch, ). The transmitted and reflected pulses through and from the sample are detected to extract the time‐ and frequency‐domain responses (Yardimci, Cakmakyapan, Hemmati, & Jarrahi, ; Yardimci & Jarrahi, ). Because of these specifications, there has been great interest in predicting plant water status using THz‐TDS systems (Table ; Hu & Nuss, ; Hadjiloucas, Karatzas, & Bowen, ; Jördens, Scheller, Breitenstein, Selmar, & Koch, ; Castro‐Camus, Palomar, & Covarrubias, ; Gente et al, ; Born et al, ; Gente, Rehn, & Koch, ; Santesteban et al, ; Baldacci et al, ; Gente et al, ).…”
Section: Introductionmentioning
confidence: 99%